The effect of kebon kongok waste disposal sites on ground water quality in Suka Makmur Village, West Lombok District - Tina Melinda; Taufik Abdullah; Dilla Rahmayanti (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
The Kebon Kongok waste disposal sites (WDS), Suka Makmur Village, is the final waste disposal site for Mataram City and West Lombok because Mataram City does not have a WDS. The condition of the WDS has exceeded its capacity. Suka Makmur Village is a village close to the Kebon Kongok WDS. This research was conducted in Suka Makmur Village to know groundwater quality with Smell, Taste, TDS, pH, BOD, COD, Ammonia (NH3N), and Total Coliform. The method used to determine the quality of groundwater is by using the Pollution Index Method. In determining the sampling technique, the purposive sampling technique is used, a determination technique with certain considerations. The results showed that the results of the analysis of raw water samples with the parameters Odor, Taste, Total Dissolved Solid, pH, BOD, COD, Ammonia (NH3N), and Total Coliform. The results obtained from the three sample points that exceeded the Water Quality Standard threshold were only the Total Coliform parameter, sample 1 was 230 mg/l, sample 2 was 91 mg/l, and sample 3 was 230 mg/l based on the Regulation of the Minister of Health of the Republic of Indonesia Number 32 2017 concerning Environmental Health Quality Standards and Water Health Requirements for Sanitation Hygiene, Swimming Pools, Solus Per Aqua, and Public Baths. Based on the results of data analysis using the Pollution Index Method (IP), sample one was 3.14, sample two was 1.68, and sample three was 3.13. These results indicate that the condition of the water is included in the Light Polluted category based on the Decree of the State Minister for the Environment Number 115 of 2003 concerning Water Quality Status, the Pollution Index value with an IP score of 1.1 - 5.0 is intended for class I water.